Timing of cannulation of arteriovenous grafts: are we too cautious? - Al Shakarchi, Julien (Clin Kidney J, 2015)
BACKGROUND: Timing of first cannulation of an arteriovenous graft has been the subject of great debate for clinicians worldwide. In this paper, we reviewed the current literature on the timing of first cannulation of arteriovenous grafts. METHODS: Searches of PubMed, Medline and the Cochrane Library were performed using specific search terms to identify articles, dealing primarily with the timing of dialysis graft cannulation. RESULTS: Following strict inclusion/exclusion criteria by two reviewers, eleven studies were included and divided into subgroups for ePTFE and new generation grafts. CONCLUSIONS: The current literature does not seem to support the current guidelines as there is no evidence to suggest that a delay in cannulation of grafts will improve graft survival and patency.